Social Norms in Networks - Philip Ushchev; Yves Zenou (Institute of Labor Economics (IZA), 2019)
Although the linear-in-means model is the workhorse model in empirical work on peer effects, its theoretical properties are understudied. In this study, we develop a social-norm model that provides a microfoundation of the linear-in-means model and investigate its properties. We show that individual outcomes may increase, decrease, or vary non-monotonically with the taste for conformity. Equilibria are usually inefficient and, to restore the first best, the planner needs to subsidize (tax) agents whose neighbors make efforts above (below) the social norms. Thus, giving more subsidies to more central agents is not necessarily efficient. We also discuss the policy implications of our model in terms of education and crime.
Keywords: D85; J15; Z13; 330; social norms; conformism; local-average model; welfare; anti-conformism; network formation